Perlindungan Hukum Melalui Pencatatan Akta Perjanjian Pengikatan Jual Beli (PPJB) Tanah di Kantor Pertanahan - Rohali, Novia (Magister Kenotariatan, Universitas Jambi, 2025)
Land is one of the important assets in people's lives that are prone to causing disputes. The Sale and Purchase Agreement (PPJB) is used as a preliminary agreement before the making of the Sale and Purchase Deed (AJB) before the Land Deed Making Office (PPAT). However, the absence of PPJB registration has the potential to cause legal uncertainty and losses for the parties. This study aims to analyze the urgency of recording PPJB Deeds at the Land Office as well as the legal consequences that arise both when the registration is done or not. The research uses normative juridical methods with a legislative and conceptual approach, as well as primary legal materials in the form of UUPA, Government Regulation Number 24 of 1997, and Ministerial Regulation of ATR/KBPN Number 16 of 2021. The results of the study show that the recording of PPJB strengthens the legal position of the parties, provides legal protection and certainty for the object of the agreement, and limits the possibility of transferring rights to other parties outside the agreement. On the other hand, without registration, PPJB remains valid as a deed of agreement, but does not provide maximum protection for the rights of the parties and has the potential to cause disputes in the future. This study recommends that PPJB registration be used as a standard practice in land purchase and sale transactions to minimize legal risks and strengthen the orderly land administration in Indonesia.